(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
Densities of binary mixtures of diethylsulfoxide with methanol or ethanol have been measured over the full range of compositions at different temperatures by means of a vibrating-tube densimeter. The excess and partial molar volumes were calculated from the density data. It has been shown that the excess molar volumes are negative over the whole range of composition and temperature and very strong molecular interactions take place between diethylsulfoxide and alkanols.